Criteria For Good Test Questions (Analysis of Writing of Islamic Junior High School Exam Questions for Arabic Language Subjects at the Ta'mirul Islam Islamic Boarding School) - Afifah, Luthfiyyah Nur (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The aim of this research was to analyze the odd exam question in Arabic subject to the ninth-grade students at Boarding School of Ta’mirul Islam Surakarta in academic year 2020/2021 which include the validity, power of difficulty, discrimination power, and answer patterns. This method used in the research was a descriptive quantitative method. The result of the analysis showed that the quality which was seen from the 1) validity there were 11 or 27,5% questions which were valid and the rest were 29 or 72,5% of questions were invalid. 2) from the level of difficulty, there were 4 or 10% of questions which average level of difficulty, and there were 32 or 90% of questions which had difficult and easy level. 3) From the discrimination power there were 10 or 25% of questions which had good discriminations and 30 or 75% of questions which had low and negative. 4) from the answer patterns, it is known that in general all distributor in the question were unfunctional properly